Native Language Interference in the spoken target language: A case study of there speakers of english as a foreign language. - Romero Espinoza, María Gabriela (2010)
Features of the native language as pronunciation, grammatical structures, vocabulary and language habits have been found to be transferred from one language to another. Linguists say that there is interference still in competent speakers of a second language. And that the only native like competence or proficiency exists in native speakers.